Wnt-Signaling and the Evolution of Embryonic Posterior Development - Martin, Benjamin L. (Curr Biol, 2009)
During vertebrate embryogenesis, most of the mesodermal tissue posterior to the head forms from a progenitor population that continuously adds blocks of muscles (the somites) from the back end of the embryo. Recent work in less commonly studied arthropods, the flour beetle Tribolium and the common house spider, provides evidence suggesting that this posterior growth process might be evolutionarily conserved, with canonical Wnt signaling playing a key role in vertebrates and invertebrates. We discuss these findings as well as other evidence that suggests that the genetic network controlling posterior growth was already present in the last common ancestor of the bilateria. We also highlight other interesting commonalities as well as differences between posterior growth in vertebrates and invertebrates, suggest future areas of research, and hypothesize that this process may facilitate evolution of animal body plans.